2018
DOI: 10.1111/jcmm.13850
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cell differentiation and proliferation lead to production of abzymes in EAE mice treated with DNA–Histone complexes

Abstract: Experimental autoimmune encephalomyelitis (EAE)‐prone C57BL/6 mice are used as a model of human multiple sclerosis. We immunize mice with myelin oligodendrocyte glycoprotein (MOG), DNA–histone and DNA‐methylated bovine serum albumin (met‐BSA) complexes to reveal different characteristics of EAE development including bone marrow lymphocyte proliferation and differentiation profiles of hematopoietic stem cells. Immunization of C57BL/6 mice with MOG35‐55 results in the acceleration of EAE development. Anti‐DNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
252
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 25 publications
(267 citation statements)
references
References 55 publications
(420 reference statements)
3
252
0
Order By: Relevance
“…Untreated control non-autoimmune CBA mice were characterized by low levels of proteinuria at three months of age (1.6 ± 0.08 mg/mL) and levels did not change remarkably over the next 45 days ( Figure 1C). Interestingly, C57BL/6 mice showed significantly higher proteinuria (up to 7.22 ± 0.9 mg/mL) at three months of age even before treatment with MOG [17,18,38,41,42]. Upon spontaneous development of EAE, levels of proteinuria almost did not change in untreated control C57BL/6 mice before day 20, and then gradually increased to 17.0 mg/mL by day 63.…”
Section: Hematopoietic Progenitor Colony Formationmentioning
confidence: 96%
See 2 more Smart Citations
“…Untreated control non-autoimmune CBA mice were characterized by low levels of proteinuria at three months of age (1.6 ± 0.08 mg/mL) and levels did not change remarkably over the next 45 days ( Figure 1C). Interestingly, C57BL/6 mice showed significantly higher proteinuria (up to 7.22 ± 0.9 mg/mL) at three months of age even before treatment with MOG [17,18,38,41,42]. Upon spontaneous development of EAE, levels of proteinuria almost did not change in untreated control C57BL/6 mice before day 20, and then gradually increased to 17.0 mg/mL by day 63.…”
Section: Hematopoietic Progenitor Colony Formationmentioning
confidence: 96%
“…We compared the development of EAE over time using previously obtained data from C57BL/6 mice and two new experimental groups: Th untreated control/Th MOG-treated mice and CBA untreated control/CBA MOG-treated mice. The same experiments were performed earlier and well-reproducible data on the analysis of all parameters for untreated control and MOG-treated C57BL/6 mice were available [17,18,41,42] for comparison with the new results.…”
Section: Choosing a Model For Studying The Mechanism Of Eae Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that anti-DNA Abs are mostly directed against histone-DNA complexes appearing in blood during cell apoptosis [29]. IgGs purified from blood sera of HIV-infected [27] and MS [30] patients as well as EAE-prone mice [28] efficiently hydrolyze from one to five human histones (H1, H2a, H2b, H3, and H4). However, proteolytic activity auto-IgGs against histones from CSFs of patients with MS in the hydrolysis of five histones has not been previously studied.…”
Section: Evidence Of Histone-hydrolyzing Activity Directly To Antibodiesmentioning
confidence: 99%
“…It was recently shown that in contract to healthy humans, 100% of IgGs purified from the sera of 32 HIV-infected patients efficiently hydrolyze from one to five human histones (H1, H2a, H2b, H3, and H4) [27]. In addition, the blood and brain of experimental autoimmune encephalomyelitis (EAE)-prone C57BL/6 mice contain auto-Abs against histones effectively hydrolyzing these proteins [28]. Many anti-DNA Abs are directed against nucleosomal histone-DNA complexes appearing during cell apoptosis [29].…”
mentioning
confidence: 99%